Shear strength and compressibility behaviour of lime-treated organic clay - Yunus, N. Z. M. (Springer Verlag, 2016)
Apart from strength characteristics, a review of studies on the compressibility of lime-treated soils is equally important that influenced the stability of soil structures. Due to the fact that no study has been carried out, an investigation on the effects of humic acid on strength and compressibility behaviour of lime-stabilised organic clay is presented in this paper. Unconfined Compressive Strength (UCS) and oedometer tests were carried out at different curing periods of 7, 28 and 90 days. Consolidation data was analysed in terms of changes in void ratio (e), volumetric strain (ε1), compression index (Cc), and coefficient of consolidation (cv) which defines a soil’s compressibility. The results showed a similar behaviour when compared to both tests. It can be conclude that the cementation bonding was associated with the fabric arrangement of soil structures.